The Effectiveness of Problem Based Learning Toward Students’ Science Learning Outcomes - Astuti, Agung Yulia; Wibawa, I Made Citra; Suarjana, I Made (Universitas Pendidikan Ganesha, 2020)
Science learning outcomes of fourth grade students in elementary schools still tend to be low. The learning model used by teachers still dominates conventional learning. ThisThis research is a quasi-experimental (Quasi Experiment), with a Non Equivalent post-test only control group design. The population in this study were all grade IV elementary school students, and by using the random sampling method, two research samples were obtained, the experimental group and the control group class. Multiple choice tests were chosen as a method of data collection, for the analysis of the data in this study descriptive statistical analysis techniques and t-tests were used. After analyzing the data, the result of tcount (4.84) <ttable (2.01) shows that the Problem Based Learning model has a significant effect on the science learning outcomes of Grade IV students. Based on the results of research that has been done the Problem Based Learning model has a significant effect on the learning outcomes of Natural Sciences.